Quantum algorithms for simulating quantum systems - McArdle, S (2021)
Conventional computers are invaluable tools for analysing and predicting the behaviour of the world around us; from the formation of the Universe at large, to the motion of subatomic particles. Unfortunately, the latter problem has proved exceedingly difficult to simulate accurately, due to the computational complexity allowed by the laws of quantum mechanics. There have been a number of proposals to `fight fire with fire' -- to use quantum computers to efficiently simulate quantum systems of interest. State-of-the-art resource estimates suggest that it may be possible to simulate classically intractable systems using hundreds of thousands, or millions, of physical qubits. Unfortunately, such resources are beyond our current capabilities -- and may remain so for the foreseeable future.